2019
DOI: 10.1016/j.rbmo.2019.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Chemosensitivity and chemoresistance in endometriosis – differences for ectopic versus eutopic cells

Abstract: RESEARCH QUESTION Endometriosis is a common gynecological disease defined by the presence of endometrium-like tissue outside uterus. This complex disease, often accompanied by severe pain and infertility, causes significant medical and socioeconomic burden; hence, novel strategies are sought for treatment of endometriosis. Here, we set out to explore cytotoxic effects of a panel of compounds to find toxins with different efficiency in eutopic versus ectopic cells, thus highlighting alterations in the correspon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 64 publications
(76 reference statements)
1
14
0
Order By: Relevance
“…The cells were incubated with individual compounds or mixtures for 48 h, and viability assay was then carried out according to the previously published protocol 77 (see details under the Supplementary Methods ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cells were incubated with individual compounds or mixtures for 48 h, and viability assay was then carried out according to the previously published protocol 77 (see details under the Supplementary Methods ).…”
Section: Methodsmentioning
confidence: 99%
“…The final volume per well was 1 mL, and the concentration of DMSO in the treated wells was 0.1% by volume. Following the post-treatment, the cells were grown for another 48 h, and viability assay was then carried out according to the previously published protocol 77 (see details under the Supplementary Methods ).…”
Section: Methodsmentioning
confidence: 99%
“…The general protocol of the resazurin assay was published previously [10]; the experimental details are listed below.…”
Section: Resazurin Assaymentioning
confidence: 99%
“…The spectra were recorded following the viability studies (as described in Section 2.2.1) at 30 • C or 37 • C using the following parameters: (A) fluorescence intensity-excitation at 540 (10) nm, emission scanned within the range of 570 to 700 nm or 580 to 700 nm (step of 2 nm) using a monochromator, top optics, gain 50, and a read height of 8.5 mm; (B) absorbance-within the range of 300 to 700 nm (step of 5 nm) using a monochromator.…”
Section: Measurement Of Absorbance and Fluorescence Spectramentioning
confidence: 99%
“…We have also recently demonstrated cellpenetrating peptide and siRNA-mediated therapeutic effects on endometriosis models and proposed a novel therapeutic target, ribonucleotide reductase for the treatment of endometriosis [57]. In addition, we have previously identified miRNAs that are differentially expressed in ectopic endometriotic stromal cells [58] and found that some anticancer drugs, such as doxorubicin, are selectively cytotoxic to ectopic endometrial cells [59]. Affinity-targeting of such drugs using nanoformulations could be an efficacious strategy to potentiate their activity of specifically depleting endometriotic lesions.…”
Section: Pl1 Conjugation Increases the Effect Of Cytotoxic Nanoparticles In 12z And Hesc Cellsmentioning
confidence: 99%